Genomic assessment and phenotypic characteristics of F2 resource sheep population - T. E. Deniskova; A. V. Dotsev; S. N. Petrov; M. S. Fornara; H. Reyer; K. Wimmers; V. A. Bagirov; G. Brem; N. A. Zinovieva (Аграрная наука Евро-Северо-Востока)
The article presents the results of assessment of genetic diversity and Principal Component Analysis (PCA) in the re-source sheep population, originated from crossing of fast-growing (Katahdin) and slow growing (Romanov) breeds for QTL mapping and search for candidate genes associated with growth rate. The study was conducted on 88 sheep from the resource population, including two unrelated families that have been reared in the Moscow region since 2017. Each family consists of a Katahdin ram (founder), Romanov’s ewes (mothers), F1 hybrids, and two groups of backcrosses. All sheep were genotyped using a high-density DNA chip Illumina Ovine Infinium® HD SNP BeadChip (~ 600 thousand SNP markers). SNP markers were filtered in the PLINK v.1.90. PCA was performed in PLINK v.1.90 and visualized in R package ggplot2. The genetic diversity indices (Ho, uHe, Ar, FIS) were calculated in R package “diveRsity”. It was established that both crosses had higher level of genetic diversity in comparison with the mother breed. F1 hybrids were characterized by the highest level of observed heterozygosity (Ho = 0.409-0.407), while Ho ranged from 0.382 to 0.396 for the backcrosses, respectively. The expected heterozygosity ranged from 0.329 to 0.356 in the groups from the resource population. Allelic richness was high in all studied groups (more than 1.849). PCA showed that the mated parent breeds were highly differentiated, as it should be in successful establishment of the resource population. The phenotypic characteristic of the backcrosses on live weight and nine body measurements at 9, 42 and 90 days is given. The coefficients of variation were the highest by live weight (17.0-19.0%), body length (15.5-22.3%) and oblique body length (16.2% and 22.7%) at 90 days. The results are intermediate and create a geno-typic and phenotypic base to perform GWAS at the next stage of our study.